2010
DOI: 10.1007/s00418-010-0764-0
|View full text |Cite
|
Sign up to set email alerts
|

Akt and PKC are involved not only in upregulation of telomerase activity but also in cell differentiation-related function via mTORC2 in leukemia cells

Abstract: We have shown previously that PI3K/Akt pathway is active after cell differentiation in HL60 cells. In the present study, we have investigated whether additional molecules, such as protein kinase C (PKC), are involved in the regulation, not only of telomerase, but also of leukemia cell differentiation. We show that PKC activates telomerase and is, itself, activated following VD3- or ATRA-induced differentiation of HL60 cells, as was observed for PI3K/Akt. To clarify the significance of PI3K/Akt and PKC pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The role of different PKC isozymes in granulocytic differentiation is quite controversial. For ATRA-induced granulocytic differentiation in HL-60 cells, PKCα and PKCβII are activated and positively regulate granulocytic differentiation [31]. However, Zauli G et al reported that only PKCα and PKCζ but neither PKCβII nor PKCβI showed signi cant modi cation upon ATRA treatment in HL-60 cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…The role of different PKC isozymes in granulocytic differentiation is quite controversial. For ATRA-induced granulocytic differentiation in HL-60 cells, PKCα and PKCβII are activated and positively regulate granulocytic differentiation [31]. However, Zauli G et al reported that only PKCα and PKCζ but neither PKCβII nor PKCβI showed signi cant modi cation upon ATRA treatment in HL-60 cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…When active, mTORC2 is phosphorylated on Ser2481 (Copp et al, 2009) and is important for cell survival, metabolism, proliferation, and cytoskeletal organization. mTORC2 phosphorylates Protein Kinase Cα (PKC), which regulates cell proliferation, differentiation, apoptosis, and telomerase activities and is constitutively active in hematopoetic cancers, where it promotes cell proliferation and survival (Ikenoue et al, 2008; Yamada et al, 2010; Zhang et al, 2012). Knockdown of mTORC2 components disrupts cell morphology and actin polymerization (Loewith et al, 2002; Jacinto et al, 2004).…”
Section: Mtorc2mentioning
confidence: 99%
“…17 Some studies have demonstrated that there are various PKC isoforms in the oocytes and zygotes. [19][20][21][22][23] However, little information is available on mouse oocytes. 18 Several studies have indicated that PKC may play a role on Akt in many cell function.…”
Section: Introductionmentioning
confidence: 99%
“…18 Several studies have indicated that PKC may play a role on Akt in many cell function. [19][20][21][22][23] However, little information is available on mouse oocytes.…”
Section: Introductionmentioning
confidence: 99%